Safety and immunogenicity of the quadrivalent human papillomavirus vaccine in patients with childhood systemic lupus erythematosus: a real-world interventional multi-centre study. (July 2020) - Rotstein Grein, Ingrid Herta; Pinto, Natalia Ferreira; Lobo, Aline; Groot, Noortje; Sztajnbok, Flavio; da Silva, Clóvis Artur Almeida; Paim Marques, Luciana B; Appenzeller, Simone; Islabão, Aline Garcia; Magalhães, Claudia Saad; de Almeida, Rozana Gasparello; Bica, Blanca; et al.
Objective: This study aimed to assess the safety and immunogenicity of the quadrivalent human papillomavirus (qHPV) vaccination in childhood-onset systemic lupus erythematosus (cSLE) patients. Methods: Volunteer cSLE patients aged 9–20 years and healthy controls (HC) were enrolled to receive a two- or three-dose qHPV vaccination schedule from March 2014 to March 2016. Study visits were performed before the first dose, one month after the second and third doses and one year after the first dose. In each study visit, disease activity and adverse events following vaccination were analyzed, and a serum sample was collected for testing antibody concentrations. Participant recruitment was conducted in 15 Brazilian paediatric rheumatology units. Of the 256 cSLE patients included, 210 completed the two- or three-dose schedules; 15 had previously received one dose, and 18 had received two doses of the vaccine. The analysis was based on intention-to-treat so that participants who did not complete the entire study protocol were also included. Results: No severe adverse events were related to the vaccination. Disease activity was generally low and remained stable or even improved. The HC presented 100% seropositivity to HPV16 and HPV18, whereas the two- and three-dose cSLE groups presented 93% and 83% versus 97% and 91%, respectively. One year after the first dose, seropositivity of the three-dose cSLE group was 91% to HPV16 and 84% to HPV18. Conclusions: HPV vaccination in cSLE patients is safe and immunogenic. Since the seropositivity to HPV16 and HPV18 was higher for the three-dose schedule group, this regimen should be recommended for cSLE patients.